Перспективи розвитку dark-туризму в Україні - Філатов, Єгор Максимович; Filatov, Y. M. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Кваліфікаційну роботу присвячено аналізу сучасного стану та обґрунтуванню перспектив розвитку dark-туризму в Україні. У дослідженні розглянуто теоретичні основи поняття dark-туризму, його види, функції та особливості як складової туристичної індустрії. Проаналізовано міжнародний досвід організації dark-туризму та визначено найуспішніші практики. У роботі досліджено ресурси dark-туризму в Україні за видами та їх регіональну специфіку. Проведено оцінку сучасного рівня розвитку темного туризму, динаміку відвідуваності об’єктів, розкрито проблеми нормативно-правового забезпечення та організації безпеки в цій сфері. Обґрунтовано основні напрями перспективного розвитку dark-туризму в Україні як інструменту збереження історичної пам’яті та відновлення економіки після війни.

This paper is devoted to the analysis of the current state and justification of the prospects for the development of dark tourism in Ukraine. The paper explores the theoretical foundations of dark tourism, its types, functions, and characteristics as part of the tourism industry. International experience in the organization of dark tourism and the most successful practices are analyzed. The study examines the resources of dark tourism in Ukraine by type (disaster zones, cemeteries, fortifications, sites of tragedy, etc.) and their regional features. The work includes an assessment of the current level of dark tourism development, visitor dynamics, and identifies issues related to legal regulations and safety management. The paper substantiates the main directions for the future development of dark tourism in Ukraine as a tool for preserving historical memory and supporting post-war economic recovery.
Prospects for the development of dark tourism in Ukraine
Керівник: Посохов Іван Сергійович, кандидат історичних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES::Social sciences::Political science; SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Other social sciences::Public sector research; SOCIAL SCIENCES::Other social sciences::Military intelligence and security service; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production; HUMANITIES and RELIGION::History and philosophy subjects::Historical cultures; LAW/JURISPRUDENCE; Україна; dark-туризм; туристична індустрія; міжнародний досвід організації dark-туризму; ресурси dark-туризму в Україні; нормативно-правове забезпечення; безпека в сфері dark-туризму; збереження історичної пам’яті; відновлення економіки після війни; Ukraine; dark tourism; tourism industry; International experience in the organization of dark tourism; resources of dark tourism in Ukraine; legal regulations; safety management; preserving historical memory; supporting post-war economic recovery